Characterization of a novel subtype of hippocampal interneurons that express corticotropin‐releasing hormone. Issue 1 (24th July 2015) - Hooper, Andrew; Maguire, Jamie
ABSTRACT: A subset of corticotropin‐releasing hormone (CRH) neurons was previously identified in the hippocampus with unknown function. Here we demonstrate that hippocampal CRH neurons represent a novel subtype of interneurons in the hippocampus, exhibiting unique morphology, electrophysiological properties, molecular markers, and connectivity. This subset of hippocampal CRH neurons in the mouse reside in the CA1 pyramidal cell layer and tract tracing studies using AAV‐Flex‐ChR2‐tdTomato reveal dense back‐projections of these neurons onto principal neurons in the CA3 region of the hippocampus. These hippocampal CRH neurons express both GABA and GAD67 and using in vitro optogenetic techniques, we demonstrate that these neurons make functional connections and release GABA onto CA3 principal neurons. The location, morphology, and importantly the functional connectivity of these neurons demonstrate that hippocampal CRH neurons represent a unique subtype of hippocampal interneurons. The connectivity of these neurons has significant implications for hippocampal function. © 2015 Wiley Periodicals, Inc.